Blink: The Power of Thinking Without Thinking - Malcolm Gladwell (London Penguin Books, 2007)
An art expert sees a ten-million-dollar sculpture and instantly spots it's a fake. A marriage analyst knows within minutes whether a couple will stay together. A fire-fighter suddenly senses he has to get out of a blazing building. A speed dater clicks with the right person ... This book is all about those moments when we 'know' something without knowing why. Here Malcolm Gladwell explores the phenomenon of 'blink', showing how a snap judgement can be far more effective than a cautious decision. By trusting your instincts, he reveals, you'll never think about thinking in the same way again.
Keywords: Business; Nonfiction; Psychology; Sociology; Self Help